Recycling and remanufacturing or technology upgrading? emission reduction decisions of supply chain under carbon cap-and-trade mechanism - Xiaoyuan Wu; Wenqing Miao; Xingxian Zhang; Wenjin Zuo; Bingliang Shen (PLoS ONE, 2025)
Cap-and-trade mechanism can efficiently reduce carbon emissions, which makes it widely used around the world. This paper builds a Stackelberg game model for a manufacturer-led secondary supply chain and analyzes the best pricing, carbon reduction strategies, and the impacts of each variable on equilibrium results when using two emission reduction methods, recycling & remanufacturing, and technology upgrading under the cap-and-trade mechanism. The relationship between the variables was verified through case studies, and the economic benefits and emission reduction effects of the two emission reduction methods were compared. It is found that manufacturers’ profit in the recycling and remanufacturing mode is higher compared to that of the technology upgrading mode when consumer price sensitivity coefficient is low, but its emission reduction effect is less effective; raising the price of carbon trading can effectively increase the carbon reduction per unit low-carbon products and reduce total carbon emissions under the two modes. The government should boost the price of carbon to promote enterprises to reduce emissions, and it can also guide manufacturers to choose the technology upgrading emission reduction mode through other ways to minimize the total carbon emissions.